Separate and Unequal in the Labor Market: Human Capital and the Jim Crow Wage Gap - Carruthers, Celeste K.; Wanamaker, Marianne H. (Journal of Labor Economics, 2017)
Competing explanations for the long-standing gap between black and white earnings attribute different weight to wage discrimination and human capital differences. Using new data on local school quality, we find that human capital played a predominant role in determining 1940 wage and occupational status gaps in the South despite entrenched racial discrimination in civic life and the lack of federal employment protections. The resulting wage gap coincides with the higher end of the range of estimates from the post–Civil Rights era. We estimate that truly “separate but equal” schools would have reduced wage inequality by 29%–48%.